Self-Study Courses on Physical Training and Sports Activities in the Conditions of Credit-Modular System of Teaching (The Peerian Journal, 2022)
Year by year various forms of physical exercises appear and develop and new physical activities and exercises are improved. The article presents the results of studies of stu-dents’ preferences in the choice of different means of physical culture and sport to better health outcomes and the formation of physical culture of the individual